Generalized Gibbs-Thomson equation for nanoparticles at grain boundaries. (1st May 2017) - Lin, M.; Gottstein, G.; Shvindlerman, L.S.
Abstract: A general Gibbs-Thomson equation is derived from the complete free energy description of precipitates at grain boundaries, taking into account the excess free energy of the grain boundary – phase boundary junction. In this model, the equilibrium shape of particles shows a strong dependency on the particle size, which gives rise to a deviation from the classical theory of precipitation. The influence of the line tension of triple junctions on the nucleation energy barrier is discussed. Graphical abstract: Image